50 years of rare earth research in Malaysia: Past, future trend and what is missing? A bibliometric analysis - Nurul Ain, Ismail; Mohd Amirul Mukmin, Abdullah; Mohd Aizudin, Abd Aziz; Badhrulhisham, Abdul Aziz (AIP Publishing, 2024)
The bibliometric analysis was conducted using R Bibliometrix software on 4,876 articles related to rare earth published by author from Malaysia. All the articles are indexed in Scopus from 1971 to 2023. The multidimensional analytical approach provided holistic view of the scope of rare earth research in Malaysia and its progression, the major topics, institutes, trends and gaps. Based on the general descriptive data analysis, the results showed that rare earth research has gained influence in Malaysia since 2009. A clustering analysis of the retrieved keywords showed that fiber lasers and saturable absorber in rare earth was the most frequently discussed topic. The study also revealed a major gap in this area especially on the upstream and middle stream study of rare earth. The gaps should be filled in order to position Malaysia as one of the rare earth powerhouse.